'Many are called but few are chosen' (Matt 22:14): A Well Populated Hell?. (November 2022) - O'Collins, Gerald
Does the warning that closes Matthew's version of the great banquet (Matt 22:1–14) indicate that the population of hell exceeds, even far exceeds, that of heaven? This article sets out the allegorizing account of a royal banquet found in Matthew. The second set of guests stands for members of the Church, warned in most serious, apocalyptic terms to produce good works which are worthy of their calling and which will be recognized at final judgment. Taken with similar parables in Matthew, that of the king's banquet invites an appropriate response rather than offers information, still less, precise information about the final state of all Christians and other human beings.